APPLICATION OF THE METHOT OF GRAY RELATION ANALYSIS FOR THE FORMATION OF COMPLEX ASSESSMENT AND DETERMINATION OF THE MATURITY OF THE ENTERPRISE KNOWLEDGE MANAGEMENT SYSTEM - CHAIKOVSKA, INNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The economic-mathematical model of formation of complex estimation and definition of level of risk of system of management of knowledge of the enterprise with use of the gray relational analysis and a method of the analysis of hierarchies is developed in work. An enterprise knowledge management system, an example of a "gray" system, is usually a variant of "black", in which all criteria are fuzzy, and "white", in any there is a complete set of data on criteria and constraints, are between them and is a system. with incomplete description. The proposed model consists of the following stages: problem statement; determination of criteria and indicators of knowledge management system; evaluation of indicators of the knowledge management system (in numerical form and in linguistic terms) and determination of their reference values; preliminary data processing (reduction of all indicators to one order); calculation of gray relational classes (determination of gray relational coefficients; determination of weight coefficients; determination of gray relational classes); construction of a matrix of estimates; formation of a comprehensive assessment of the knowledge management system of enterprises; determining the maturity of the enterprise for knowledge management; interpretation of the obtained results. Three general criteria and 43 indicators (in terms of quantitative and qualitative characteristics) were selected: People (11 indicators), Technology (9 indicators), Processes (23 indicators). Criterion Processes include blocks: Learning (2 indicators), Innovation (5 indicators), Innovation processes (7 indicators), Innovation cooperation (2 indicators), Core activity (7 indicators). The model consists of constituent elements (people, technologies, processes), levels (individual, group, organizational, inter-organizational), stages (phases) of knowledge management (Formation – accumulation, exchange – generation – storage and documentation – use – result of knowledge management) and allows the interaction of the level of maturity of the enterprise for knowledge management. The weights of the criteria and indicators of knowledge management of the enterprise analysis of the definition system occur using the method of hierarchy (pairwise comparison method). The practical implementation of the model was implemented for public utilities of Ukraine. The developed model is universal and can be used for enterprises of different spheres of activity to comprehensively assess the knowledge management system in comparison with the benchmark enterprise, determine the level of maturity of the enterprise with management and identify problems of effective management decisions to improve competitiveness.